(untitled) (TEST Ticontre. Theory Text Translation, 2024)
Starting from the reconstruction of the literary context and the theoretical assumptions that derive from it, the article aims to analyze the “paradox of consciousness” in David Foster Wallace’s The Suffering Channel. It is a vicious circle in which the exaggeration of self-awareness leads to its semantic opposite, oblivion, understood in the dual sense of “unconsciousness, unawareness” and “heedlessness” (designating an attitude of indifference and inattention). The linguistic representation of this narcissistic mental loop, which alienates the characters from the intersubjective environment and makes every attempt at communication self-referential and futile, is offered by the relational mechanisms of identity performance and dialogic manipulation. The paradoxical logic of oblivion is also systematically configured within a “rhetoric of reticence”, so that the crucial facts of the story are only indirectly evoked, through ellipses and allusions that, by determining the lacunarity of the narrative, reflect the lacunarity of consciousness. Through textual analysis, the article will therefore examine the concept of “oblivion” understood as a constant thematic and stylistic feature. A partire dalla ricostruzione del contesto letterario e dei presupposti teorici che da esso scaturiscono, l’articolo si propone di analizzare il “paradosso della coscienza” in The Suffering Channel di David Foster Wallace. Si tratta di un circolo vizioso secondo cui l’esasperazione dell’autocoscienza conduce al suo opposto semantico, all’oblio inteso nel duplice senso di “unawareness” (che indica uno stato di “inconsapevolezza”) e “heedlessness” (che designa un atteggiamento di indifferenza e disattenzione). Del narcisismo, che aliena i personaggi dall’ambiente intersoggettivo e rende autoreferenziale e velleitario ogni tentativo di comunicazione, i meccanismi relazionali della performance identitaria e della manipolazione dialogica offrono la rappresentazione linguistica. La logica paradossale dell’oblio è inoltre sistematicamente configurata entro una “retorica della reticenza”, per cui i fatti cruciali della storia vengono evocati soltanto indirettamente, attraverso ellissi ed allusioni che, determinando la lacunosità della narrazione, rispecchiano la lacunosità della coscienza. Tramite l’analisi testuale, l’articolo analizzerà quindi il concetto di “oblio” inteso come costante tematica e costante stilistica.